If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 6) + 2x = 90 Reorder the terms: X + (6 + x) + 2x = 90 Remove parenthesis around (6 + x) X + 6 + x + 2x = 90 Reorder the terms: 6 + X + x + 2x = 90 Combine like terms: x + 2x = 3x 6 + X + 3x = 90 Solving 6 + X + 3x = 90 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + X + -6 + 3x = 90 + -6 Reorder the terms: 6 + -6 + X + 3x = 90 + -6 Combine like terms: 6 + -6 = 0 0 + X + 3x = 90 + -6 X + 3x = 90 + -6 Combine like terms: 90 + -6 = 84 X + 3x = 84 Add '-3x' to each side of the equation. X + 3x + -3x = 84 + -3x Combine like terms: 3x + -3x = 0 X + 0 = 84 + -3x X = 84 + -3x Simplifying X = 84 + -3x
| -4n+8=7n+10 | | y=(y^4) | | 4n+2-5=7+n+2 | | y=0.5(3/4) | | 4x-1=61 | | y=5x^4-5x | | 49y+6y-5= | | 14=2/3(y-15) | | (2x)+(x+12)+(196)=180 | | 111111111*111111111=12345678987654321 | | 2/3m=15 | | 1/2x2-5=5 | | 6x+16-15=2 | | -3(x+7)-45=1-52 | | 5a-12=-3a+14 | | y=(7/8) | | X/-4=-2-(-3) | | (a^-1•b^4)/(b^-2•c^3) | | 2x^2-4x-174=0 | | X/-4=-2(-3) | | 121=(15-z)+(-3x) | | 7/8p-4=12 | | 22x-7x-2=0 | | X+6=24(x+8) | | M=t-c-s | | 2x^2+4x-174=0 | | 43y=21(2y+1) | | 5m-1=7m-2 | | x/2x-8÷5/3x-12 | | -2z^2-(2-I)z+i=0 | | 12-11=x/-6 | | 2w+12=4w+0 |